The Go-Public Policy and Its Impact to the Indonesian Islamic Bank Soundness - Aini Masruroh; Hasbi Siraj (ETIKONOMI, 2016)
The needed of big fund inspired the companies to sell a part of its shares in the capital market. One of methods that used is to be a public company (Go-Public). However, for Islamic banking to be a public company is not main choice. At present, Islamic banking that was listing its shares in Indonesian Stock Exchange is one Islamic banking only. In this research described the comparison financial soundness of Islamic banking pre- Go-Public with post- Go-Public. The used of the analysis was the analysis of financial ratios of components contained in RBBR (Risk-based Bank Rating). Comparing between a financial soundness of Islamic banking pre go-public and post go-public used comparison test Paired-sample t test. The financial soundness condition of Islamic banking pre- and post- Go-Public overall changed to a better level. However, based on the result of further tests, showed that Go-Public policy only influenced to capital factor. DOI: 10.15408/etk.v15i1.2410